Characterization of a genetically engineered mouse model of hemophilia A with complete deletion of the F8 gene. (8th January 2016) - Chao, B. N.; Baldwin, W. H.; Healey, J. F.; Parker, E. T.; Shafer‐Weaver, K.; Cox, C.; Jiang, P.; Kanellopoulou, C.; Lollar, P.; Meeks, S. L.; Lenardo, M. J.
Abstract : Essentials Anti‐factor VIII (FVIII) inhibitory antibody formation is a severe complication in hemophilia A therapy. We genetically engineered and characterized a mouse model with complete deletion of the F8 coding region. F8 TKO mice exhibit severe hemophilia, express no detectable F8 mRNA, and produce FVIII inhibitors. The defined background and lack of FVIII in F8 TKO mice will aid in studying FVIII inhibitor formation. Summary: Background: The most important complication in hemophilia A treatment is the development of inhibitory anti‐Factor VIII (FVIII) antibodies in patients after FVIII therapy. Patients with severe hemophilia who express no endogenous FVIII (i.e. cross‐reacting material, CRM) have the greatest incidence of inhibitor formation. However, current mouse models of severe hemophilia A produce low levels of truncated FVIII. The lack of a corresponding mouse model hampers the study of inhibitor formation in the complete absence of FVIII protein. Objectives: We aimed to generate and characterize a novel mouse model of severe hemophilia A (designated the F8 TKO strain) lacking the complete coding sequence of F8 and any FVIII CRM. Methods: Mice were created on a C57BL/6 background using Cre‐Lox recombination and characterized using in vivo bleeding assays, measurement of FVIII activity by coagulation and chromogenic assays, and anti‐FVIII antibody production using ELISA. Results: All F8 exonic coding regions were deleted from the genome and no F8 mRNA was detected in F8 TKO mice. The bleeding phenotype of F8 TKO mice was comparable to E16 mice by measurements of factor activity and tail snip assay. Similar levels of anti‐FVIII antibody titers after recombinant FVIII injections were observed between F8 TKO and E16 mice. Conclusions: We describe a new C57BL/6 mouse model for severe hemophilia A patients lacking CRM. These mice can be directly bred to the many C57BL/6 strains of genetically engineered mice, which is valuable for studying the impact of a wide variety of genes on FVIII inhibitor formation on a defined genetic background.